Thermal and morphological study of chitosan metal complexes - Pereira, Fernanda Stuani [UNESP]; Lanfredi, Silvania [UNESP]; Perez Gonzalez, Eduardo Rene [UNESP]; Silva Agostini, Deuber Lincon da [UNESP]; Gomes, Homero Marques [UNESP]; Medeiros, Ricardo dos Santos [UNESP] (Springer, 2017)
The synthesis of chitosan Schiff bases, N-benzylidene chitosan (CTB), 4-dimethylamino-benzylidene chitosan (CTDB) and 4-nitro-benzylidene chitosan (CTNB), and their interaction with Cu2+, Zn2+ and Ni2+ were studied. The content of metal ions was determined by atomic absorption spectrometry, and the results showed that chitosan exhibited higher chelating capacity for the metal ions. Morphological changes of Schiff bases and complexes were demonstrated by SEM images. The presence of crystals attributed to copper sulfate adsorbed on the polymers surface was also observed, which indicates that part of the metal content is in the salt adsorbed and might influence in their further application studies. X-ray diffraction patterns showed that the formation of complexes resulted in the decrease in crystallinity. The thermal behavior of derivative and metal complexes were studied by thermogravimetric analysis, differential thermogravimetric analysis and differential scanning calorimetry. The results showed that the presence of new groups and metal ions bonded to chitosan affected their thermal stability.
Keywords: Chitosan; Schiff bases; Copper; Zinc; Nickel; Complexes